The importance of toxicological-chemical analysis in resolving deaths of unknown cause - case report - Antović, Aleksandra; Miljković, Milica; Pančić, Dimitrije; Vujović, Maja; Kostić, Emilija; Milić, Miroslav; Todorović, Stevan (Archives of Pharmacy, 2022)
Reliable forensic determination of the cause of death is performed by comparative analysis of data on the case circumstances, clinical picture, autopsy findings, and toxicologic-chemical analysis results. This case describes a previously healthy three-and-a-half-year-old girl hospitalized after a short period of fever, agitation, and convulsions. Despite adequate and prompt symptomatic therapy, the death occurred soon after the admission to hospital, without a conclusion on the possible reasons for the etiology of a presented pathological condition. External autopsy findings showed no apparent signs of violence. The internal examination showed diffuse cerebral hemorrhage, brain and lung swelling, confirmed by pathohistological exam. Toxicologic-chemical analysis of cadaveric liquids and tissues samplings, using the technique of gas-mass chromatography and liquid chromatography with the flame ionizing detector, determined the presence of theophylline, the active metabolite of aminophylline, in a concentration of 83.64 mg/L (toxic concentration: above 20 mg/L), as well as phenobarbitone and thiopental in therapeutic concentrations. The conclusion was that the death is violence caused by aminophylline poisoning. Investigative authorities established that the child, without the supervision of the elderly, consumed a large amount of aminophylline tablets orally. Prosecution was filed against the parents for neglecting a minor. This specific case emphasis the significant role of the toxicologic-chemical results in complete autopsy findings (macroscopic and microscopic) which must be a fundamental part of medico-legal closure of the determination of the cause of death.